STRATEGI DIRECTED READING THINKING ACTIVITY (DRTA) MELALUI EKSPLORASI KETERAMPILAN MEMBACA NARASI DONGENG TRADISIONAL PADA SISWA KELAS III SEKOLAH DASAR - Ratna Sari, Hesti; Siti Rochmiyati; Moh. Rusnoto Susanto; Sutrisna Wibawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Based on the results of the evaluation of the reading comprehension skills of class III students at Tukangan State Elementary School, it was stated that the reading comprehension skills of class III students at Tukangan State Elementary School were still lacking. Thus, this research aims to improve reading comprehension skills in fairy tales using the Directed Reading Thinking Activity (DRTA) strategy for class III students at SD Negeri Tukangan Yogyakarta. This type of research is collaborative classroom action research. This research was carried out at Tukangan Yogyakarta State Elementary School with the research subjects being all 20 grade III students at Tukangan Yogyakarta State Elementary School, consisting of 10 male students and 10 female students. In this research, researchers used an action research design developed by Kemmis and Taggart with a spiral model. The data collection methods used are tests, observation and documentation. The data analysis technique in this research is quantitative descriptive statistics, namely by finding the average. The results of the research show that learning fairy tale reading comprehension skills using the Directed Reading Thinking Activity (DRTA) strategy can improve the fairy tale reading comprehension skills of third grade students at SD Negeri Temanan Yogyakarta. The increase in fairy tale reading comprehension skills up to cycle I, meeting 2 was 7.85, from the initial condition of 60.20, it increased to 68.05. In cycle II, meeting 2, it increased by 15.45, from the initial condition of 60.20 it increased to 75.65.